Variabilidade fenotípica entre populações de uma espécie de anfípode troglóbio de Presidente Olegário - MG - Borges, Rayssa Karolina Ferreira (2020)
Directional pressure caused by the main features of the underground environment, such as the absence of light and oligotrophy, have always been the premises for the modification found in specialized organisms at these sites. However, new research show that habitats within the cave environment, such as puddles and rivers, can also act as drivers for the existing morphological differences. Some organisms are typically found in hypogean environments, including some amphipod crustaceans. Among the few amphipod species listed to Brazilian caves, only one is known to occur in more than one cave and in different habitats, Hyalella veredae, which enables the opportunity to evaluate the pressures on the morphology of this species. The objective of this research was to assess if the morphologies observed on the troglobite Hyalella veredae can be associated to habitat variation, and not only to the hypogean environment per se, considering the four caves where it is distributed. The organisms were collected in 2013, 2014 and 2019 at Presidente Olegário municipality, Minas Gerais state, and the habitats were characterized as lentic or lotic. The crustaceans were taken to the laboratory to evaluate the troglomorphic traits related to the eyes, antenna and pereopods (IV to VII). The structures were photographed and measured. The ratios between head length and eye size, and the ratios between body length and the other structures sizes were used on statistical analyses. We used Mann-Whitney to compare morphological and habitat data, followed by PCA to visually observe the connections. The organisms differed significantly in relation to the habitat, mainly on the eyes (P < 0.001); antenna 1 (p= 0.005); antenna 2 (p < 0.001); and pereopods IV, V and VII (p= 0,019; p= 0,033; 0,009, respectively). The longer antenna, biggest eyes and shorter pereopods were associated to lotic environments, while the opposite was related to lentic environments. The PCA showed that similar habitats produced morphologically similar organisms. There was a morphological overlap, probably associated to the appendices that did not differentiate between habitats. Our results indicate that morphological differences could be associated to habitats; structure reduction could be related to the waterflow that can damage the appendages; and structure elongation is related to perception of the stimuli on the environment. The eye size differences should be associated to the light gradient inside the cave, as the organisms bearing bigger eyes were found at the twilight zone. The phenotypical variation in Hyalella veredae can derive from this species plasticity, since it showed some ability to adapt to the variable cave environments.